EDUKASI PENGGUNAAN ALAT PELINDUNG DIRI DAN PENERAPAN PERSONAL HIGIENE PADA PEKERJA INDUSTRI RUMAH TANGGA PANGAN - Fea Firdani; Putri Nilam Sari; Azyyati Ridha Alfian (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
Safe and quality food is the human right, including food products produced by the Food Household Industry. This activity aims to provide education on the use of personal protective equipment (PPE) and the application of personal hygiene to workers of the Dry Noodle the food Household Industry in Payakumbuh City, in order to reduce the risk of contamination of processed food that can cause food poisoning. The event was held in July 2021. The activities carried out are observations to find out the compliance of workers in using PPE and apply personal hygiene, then measurement of the level of knowledge of workers about PPE and personal hygiene (pre-test), Then the attachment of posters as an educational tool to improve the knowledge and compliance of workers in using PPE and the application of personal hygiene, then the provision of PPE to workers as an example of PPE that must be used by food industry workers and the last activity is the measurement of knowledge after education (post-test). The results of the activity showed an increase in workers' knowledge about the importance of the use of PPE and the application of personal hygiene at work. With the existence of educational tools and the provision of PPE can improve worker compliance to be used at work. It is expected that similar activities can be carried out on other household-scale industries in West Sumatra.